Proposal of a novel mixed integer linear programming model for site selection of a wind power plant based on power maximization with use of mixed type wind turbines. Issue 5 (August 2020) - Ari, Emin Sertaç; Gencer, Cevriye
Several methods that have been developed to obtain energy, which is indispensable for life and whose necessity has increased geometrically in the course of time, are no longer sustainable. Therefore, human being has headed towards sustainable alternative energy sources. Wind has been one of the most interested renewable energy sources for human as of the beginning of the 20th century. This study focuses on one of the most important work items at the establishment phase of this important energy source, power plant site selection. Within the scope of linear programming perspective, two models were presented based on mixed integer linear programming. The first model provides employment of single-type wind turbine on the selected site, whereas the second model, which was developed within the current study, aims additional increase in total power output by allowing employment of multiple-type wind turbine on the selected site. The same region showed up as the most appropriate site to establish wind power plant as a result of both models of the study.